Optimasi Rute Multiple Travelling Salesman Problem Distribusi Produk PT Indomarco Adi Prima (Stock Point Nganjuk) menggunakan Algoritme Ant Colony Optimization dan Algoritme Genetika - Bisma Anassuka; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. Indomarco Adi prima (Stock Point Nganjuk) is a company engaged in the distribution sector. Good transportation and distribution are important in a distribution company, where products can be delivered to consumers in good conditions, at the designated place and on time. Product distribution from PT. Indomarco Adi Prima (Stock Point Nganjuk) to consumers through stores on a large scale is a fairly complex problem, because there are many locations that must be visited. This problem and involves many sales called the Multiple Traveling Salesman Problem. Inappropriate route selection can reduce efficiency in the distribution process. So, it is necessary to make optimization to get the optimal route. This research is an attempt to optimize the route using the hybrid ant colony optimization (ACO) algorithm and genetic algorithm, so that it can determine the shortest route that will be passed by sales to retail stores. The test results show that the hybrid ant colony optimization (ACO) algorithm and genetic algorithm are able to produce a 74,3% better route than the previous route with a total distance difference of 709.219km. The optimal parameters obtained are the maximum ACO iteration of 100, the number of GA generations of 20, the number of ants is equal to the point of each salesman, a combination of Î±= 0.4 and Î²= 0.8, a combination of Cr= 1, and Mr= 0.6, so that the total distance average is 244.849 km and the fitness value is 0.040841.